PENERAPAN EVIDENCE BASED PRACTICE (EBP) TERAPI SPIRITUAL EMOTIONAL FREEDOM TECHNIQUE (SEFT) DALAM MENGATASI KECEMASAN PADA LANSIA DENGAN HIPERTENSI - Mustandhifa, Atqiya; Lestari, Puspita Hanggit (Jurnal Fisioterapi dan Kesehatan Indonesia, 2024)
Hypertension is a fatal disease that does not cause symptoms in sufferers and if blood pressure is not controlled continuously it can cause complications. One of the factors that causes blood pressure to increase is individual anxiety and stress, and hypertension can trigger anxiety in hypertension sufferers. Spiritual Emotional Freedom Technique (SEFT) intervention can be a therapy for hypertensive elderly with anxiety. This application aims to reduce anxiety levels in hypertensive patients through the application of SEFT. This type of scientific work is a case study managing three clients in RW 02, Jatiwarna Village through the EBP stages. Based on the research results, it was found that three clients experienced a decrease in anxiety levels, one client before therapy had a severe anxiety level (score 28) and after therapy the anxiety level became moderate anxiety (score 23); client two went from before therapy with a moderate level of anxiety (score 22) to a mild level of anxiety (score 14); and in three clients from before therapy with a moderate level of anxiety (score 26) to a mild level of anxiety (score 20). The conclusion from the application of SEFT therapy can reduce anxiety levels and blood pressure in hypertensive elderly with anxiety.